2022
DOI: 10.1038/s41598-022-14846-y
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal administration of mesenchymal stem cells modulates lung macrophage polarization and exerts anti-asthmatic effects

Abstract: Mesenchymal stem cells (MSCs) possess immunomodulatory properties that have therapeutic potential for the treatment of inflammatory diseases. This study investigates the effects of direct MSC administration on asthmatic airways. Umbilical cord MSCs (ucMSCs) were intratracheally administered to six-week-old female BALB/c mice sensitized and challenged with ovalbumin; airway hyperresponsiveness (AHR), analyses of airway inflammatory cells, lung histology, flow cytometry, and quantitative real-time PCR were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…On the contrary, M2-type macrophages secrete anti-inflammatory factors, such as IL-4, IL-10, IL-13, TGF- β , and VEGF, to reduce the inflammatory response, which plays a vital role in the normal repair of the tissues [54]. Interestingly, this study found that transplanting melatonin-pretreated HucMSCs allowed the recruitment of more macrophages to the injured tissues and promoted macrophage transformation from the M1 to M2 phenotypes [19, 55]. Moreover, it up-regulated the expression of anti-inflammatory factors and downregulated the expression of pro-inflammatory factors, which provides a better microenvironment for endometrial regeneration [56].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, M2-type macrophages secrete anti-inflammatory factors, such as IL-4, IL-10, IL-13, TGF- β , and VEGF, to reduce the inflammatory response, which plays a vital role in the normal repair of the tissues [54]. Interestingly, this study found that transplanting melatonin-pretreated HucMSCs allowed the recruitment of more macrophages to the injured tissues and promoted macrophage transformation from the M1 to M2 phenotypes [19, 55]. Moreover, it up-regulated the expression of anti-inflammatory factors and downregulated the expression of pro-inflammatory factors, which provides a better microenvironment for endometrial regeneration [56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MSCs can attenuate the pattern of proinflammatory cytokines in the animal model of chronic cigarette smoke exposure [175]. Furthermore, MSC-based therapy can modulate both the expression of miR-193b-5p, leading to the attenuation of sepsisinduced acute lung injury [176], and the polarization of lung macrophages and exerts antiasthmatic effects [177]. Moreover, there is an increase interest toward using MSCs in innovative gene vectors or drugs for cancer treatments [178].…”
Section: Most Recent Progress In the Application Of Mesenchymal Strom...mentioning
confidence: 99%
“…Meanwhile, MSCs also inhibit the proliferation of activated helper T (Th) cells (59). Mo et al found that MSCs suppressed Th2 inflammation by regulating macrophage activation via soluble mediators rather than direct cell-to-cell contact (60). Besides, the extracts of MSCs could suppress Th2 cells and reduce the expression of IL-17 and IFN-γ, which further demonstrate that MSCs inhibit Th2 cells through paracrine factors (61, 62).…”
Section: Mscs and Anti-inflammatory/ Immunoregulatorymentioning
confidence: 99%